The creation of ceramic-matrix composites of the BL group based on cBN and hightemperature hafnium or molybdenum carbides - Stratiichuk , D.A.; Turkevich, V.Z.; Slipchenko, K.V.; Bushlya , V.M. (Reports of the National Academy of Sciences of Ukraine, 2020)
Using the HPHT technology in the temperature interval 1600-2400 °C, the processes of formation of superhard ceramic-matrix composites in the cBN-HfC-(Al) and cBN-Мо2C-(Al) systems have been investigated. With the original ratio of components cBN:carbide:(Al) being 60:35:5 vol. %, using micropowders with a grain size of 1-10 μm, it has been shown that, starting from TSINT = 1600 °C and higher, there is a consolidation of structural constituents in the systems with the formation of strong interphase and interparticle contacts such as cBN-cBN, cBN-carbide, and carbide-carbide. The grain structure in the entire sintering temperature range does not undergo significant changes and remains fine-grained with clear interphase boundaries. The cBN— HfC—(Al) system is characterized by the formation of the boride phase — HfB2, whereas the formation of monocarbide — MoC has been observed for the cBN-Мо2C-(Al) system. Aluminum, which is present in these systems in small quantities (5 vol. %), plays the role of a residual oxygen getter and simultaneously lowers the activation barrier, making the sintering process partially liquid-phase. Young’s modulus, as well as the hardness, shows a typical dependence on TSINT maximum at 1800—2000 °C. Laboratory tests in turning AISI 316L stainless steel (cutting speed vc = 300 m/min, feed f = 0.15 mm/rev, cutting depth ap = 0.5 mm, time 300 seconds) have demonstrated the cutting edge wear for two types of composites in the range of 60—90 mkm, which indicates that this type of materials is promising as a metalworking tool.